1999
DOI: 10.1074/jbc.274.44.31463
|View full text |Cite
|
Sign up to set email alerts
|

Role of Human Cds1 (Chk2) Kinase in DNA Damage Checkpoint and Its Regulation by p53

Abstract: In response to DNA damage, mammalian cells adopt checkpoint regulation, by phosphorylation and stabilization of p53, to delay cell cycle progression. However, most cancer cells that lack functional p53 retain an unknown checkpoint mechanism(s) by which cells are arrested at the G 2 /M phase. Here we demonstrate that a human homolog of Cds1/Rad53 kinase (hCds1) is rapidly phosphorylated and activated in response to DNA damage not only in normal cells but in cancer cells lacking functional p53. A survey of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 44 publications
0
83
2
Order By: Relevance
“…While many studies have investigated how CHK2 activates and stabilizes p53 [6,17,[27][28][29], the possible role of p53 in regulating CHK2 protein level or activity has not been well studied. Studies conducted in tumor cell lines and tissue specimens have previously demonstrated an inverse correlation between p53 and CHK2 expression [30,31]. However, in our previous and current studies, neither HCT116, HCT116 p53−/− nor p53 wild-type and mutant ovarian cancer cell lines demonstrated a dramatic inverse correlation of p53 and CHK2 protein levels after irofulven treatment [42].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…While many studies have investigated how CHK2 activates and stabilizes p53 [6,17,[27][28][29], the possible role of p53 in regulating CHK2 protein level or activity has not been well studied. Studies conducted in tumor cell lines and tissue specimens have previously demonstrated an inverse correlation between p53 and CHK2 expression [30,31]. However, in our previous and current studies, neither HCT116, HCT116 p53−/− nor p53 wild-type and mutant ovarian cancer cell lines demonstrated a dramatic inverse correlation of p53 and CHK2 protein levels after irofulven treatment [42].…”
Section: Discussioncontrasting
confidence: 67%
“…An inverse correlation between p53 and CHK2 expression has been reported in tumor cell lines and tissue specimens [30,31]. A recent report suggested that p53 negatively regulates CHK2 expression by modulating the function of transcription factor NF-Y [32].…”
Section: Introductionmentioning
confidence: 95%
“…Functional proteins downstream from the p53 interactive signaling pathways, such as ataxia telangiectasia mutated (ATM) and homolog of ATM (ATR), are central to the DNA damage response (Zhou and Elledge, 2000;Goodarzi et al, 2003;Dodson et al, 2004;Irarrazabal et al, 2004;Kastan, 2004;Yang et al, 2004). Further downstream targets (substrates) of ATM/ATR include the checkpoint protein kinases Chk1 and Chk2 (Ma et al, 1998;Matsuoka et al, 1998;Sanchez et al, 1999;Tominaga et al, 1999). Chk1 and Chk2 are thought to mediate different types of DNA damage to the specific cellular responses.…”
Section: Role Of P53 In Uv Irradiation-induced Dna Damagementioning
confidence: 99%
“…Activated either through phosphorylation by the upstream kinase Ataxia Telangiectasia Mutated (ATM) (Matsuoka et al, 1998) or independently of ATM (Theard et al, 2001), CHK2 undergoes oligomerization and auto-phosphorylation (Lee and Chung, 2001;Ahn et al, 2002;Xu et al, 2002). Thereafter, CHK2 spreads the damage signal by phosphorylating multiple substrates including the Cdc25A (Falck et al, 2001b) and Cdc25C (Matsuoka et al, 1998) phosphatases, BRCA1 (Lee et al, 2000), and p53 (Tominaga et al, 1999;Caspari, 2000), thereby triggering different pathways involved in growth arrest or apoptosis .…”
Section: Introductionmentioning
confidence: 99%